Computer Terminal for Blind and Visually Impaired - Bansevicius, R.; Zvironas, A.; Virbalis, J. A. (Elektronika ir Elektrotechnika, 2011)
The computer terminal is a ferromagnetic plate with spacial configuration. on which the blind moves by his finger the sensor of a ferromagnetic material. The finger feels the variations of the friction force due to variations of magnetic field and its frequency, which can represent the variations of the different visual information. The magnetic field is created by the spiral electromagnet. It is situated under all terminal and is created the sufficiently uniform magnetic field with well resolution. Analysis of the electromagnet magnetic circuit is performed. Ill. 5, bibl. 6 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.109.3.159